Pregnancy Related Complications Due To Lifestyle Modification. - Sapana Patil; Nirmal Shah; Chintan Anudhia; Ajay Patil; Foram Bhatt; Sweta Besh; Maitri Mahant; Divya Kanojiya (Journal of Coastal Life Medicine, 2023)
Worldwide, there are so many maternal deaths per year. Pregnancy-related problems are a major cause of death for women. Unfortunately, pregnancy-related complications are a common occurrence for women, and they necessitate evaluations, because they have an effect on both the mother and the embryo or foetus. An important modifiable risk factor for pregnancy problems is the unhealthful lifestyle decisions made by obstinate mothers. Smoking, drinking alcohol, and caffeine use are among the worst lifestyle choices for mothers. Maternal age is also seen as a modifiable risk factor for unfavorable pregnancy outcomes, while not being directly tied to lifestyle. The foetus is affected by maternal behaviors, sedentary lifestyle i.e. lack of exercise and diet. With a focus on the effects on birth outcomes, this article's objective is to quickly summaries the most recent research on the consequences of stress exposure and adverse emotional states (thus, anxiety and depression) during pregnancy. The focus of this review is on the connection between maternal lifestyle and unfavorable pregnancy outcomes.